Draft Genome Sequence of Stenotrophomonas maltophilia Strain 5BA-I-2, a Soil Isolate and a Member of a Phylogenetically Basal Lineage - Nunvar, Jaroslav; Elhottova, Dana; Chronakova, Alica; Schneider, Bohdan; Licha, Irena (Genome announcements, 2014)
Stenotrophomonas maltophilia is an omnipresent environmental bacterium emerging as an opportunistic human pathogen and exhibiting multidrug resistance. Here, we report the draft genome sequence of S. maltophilia strain 5BA-I-2, a soil isolate and a member of a phylogenetically basal lineage.